The History of Kambuja-Desa Modern Cambodia - Majumdar, R.C. (Brill | Manohar Publishers & Distributors, 2024)
This volume is the part of lectures delivered in 1943 under the Sir William Meyer Lectureship Series (1942-1943) at Madras. This edition is part of three-volume series, dealing with Champa (Annam), Suvarnadvipa (Malaysia), and two volumes dedicated to Cambodian studies. This book traces the history of Kambuja Desa or ancient Cambodia. It covers the influence and expansion of Indian influence, both soft and hard power, in the colonies in the Far East. The most important source that is touched by the author is the ancient inscriptions found in Cambodia. The themes that are covered in this book are the emergence of Indian expansionism into the Cambodian land. The establishment of the Funan Kingdom is also discussed, which was the first Hinduized kingdom in the Indo-China region during the first century ad. Besides that, the expansion of Angkor and a profile of the Kambuja Kingdom are also discussed in greater detail.